2016
DOI: 10.1002/ppul.23608
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a bovine antibody test for diagnosingMycobacterium aviumcomplex in patients with cystic fibrosis

Abstract: While not suited for direct diagnosis of M. avium complex due to a high number of false positive subjects, the assay proved useful at ruling out pulmonary disease. Screening sera from patients with CF could guide clinicians to focus attention on patients at higher risk of M. avium complex pulmonary disease. Pediatr Pulmonol. 2017;52:34-40. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(27 reference statements)
2
6
0
Order By: Relevance
“…This might be an inherent weakness of the test or represent the poorly understood pathogen-host interaction of the MAC pulmonary disease spectrum, which seems to range from transient colonization to invasive disease. While the consequences of identifying subclinical MAC infection are not well understood, our results are comparable to the findings we have published using a commercial IgG ELISA designed for diagnosis of latent Johne's Disease in Cattle, a disease which resembles Crohn's disease in humans [21,26]. Although MAC and M. avium spp.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This might be an inherent weakness of the test or represent the poorly understood pathogen-host interaction of the MAC pulmonary disease spectrum, which seems to range from transient colonization to invasive disease. While the consequences of identifying subclinical MAC infection are not well understood, our results are comparable to the findings we have published using a commercial IgG ELISA designed for diagnosis of latent Johne's Disease in Cattle, a disease which resembles Crohn's disease in humans [21,26]. Although MAC and M. avium spp.…”
Section: Discussionsupporting
confidence: 84%
“…In CF research, serodiagnosis for nontuberculous mycobacteria (NTM) has previously been examined using a BCG based antigen A60 [18,19] and recently by our group in patients with Mycobacterium abscessus complex (MABSC) [20] and in patients with Mycobacterium avium spp. paratuberculosis [21]. As M. avium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Nontuberculous mycobacterial (NTM) infection, currently diagnosed by culture of sputum or bronchoalveolar lavage fluid, can lead to accelerated pulmonary function decline and morbidity in CF. A commercial bovine enzyme‐linked immunosorbent assay (ELISA) for investigating antibody activity against mycobacterium avium complex (MAC) was studied in 286 patients at the Copenhagen Cystic Fibrosis Center who had a culture performed for NTM . The test, used in veterinary medicine, was modified for human use and applied to patient.…”
Section: Infectionmentioning
confidence: 99%
“…We have previously shown that serum anti-MABSC IgG antibodies rise before and during clinical infection and can be used for diagnosis, although their protective capacity is unclear, which is also the case in P. aeruginosa infection. In some cases, MABSC IgG rose several months or years before MABSC isolation in culture ( Qvist et al., 2015b ), indicating latent or subclinical infection, which is well-known to be the case for Mycobacterium tuberculosis ( Oh et al., 2020 ), and was also the seen in CF patients with MAC infection ( Qvist et al., 2017 ; Ravnholt et al., 2019 ). We also found cross-reactivity between MABSC and other NTM when measuring either anti-MABSC or anti-MAC serum IgG ( Qvist et al., 2017 ; Ravnholt et al., 2019 ), in accordance with the genetic relatedness of NTM species ( Pereira et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, MABSC IgG rose several months or years before MABSC isolation in culture ( Qvist et al., 2015b ), indicating latent or subclinical infection, which is well-known to be the case for Mycobacterium tuberculosis ( Oh et al., 2020 ), and was also the seen in CF patients with MAC infection ( Qvist et al., 2017 ; Ravnholt et al., 2019 ). We also found cross-reactivity between MABSC and other NTM when measuring either anti-MABSC or anti-MAC serum IgG ( Qvist et al., 2017 ; Ravnholt et al., 2019 ), in accordance with the genetic relatedness of NTM species ( Pereira et al., 2020 ). Interestingly, a study showed that both the presence of Mycobacterium tuberculosis infection and the Bacillus Calmette-Guérin (BCG) vaccine (composed of an inactivated Mycobacterium bovis strain), induced cross-reactive lymphocyte response against MABSC and MAC in mice and humans ( Abate et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%